Precocious Puberty: A Case Report (TAJ: Journal of Teachers Association, 2009)
A 3-year-old girl was brought to Department of Obstetrics and Gynecology for breast development and excessive vaginal discharge. Her medical history and family history were unremarkable. From investigations she was diagnosed as a case of precocious puberty. This case report emphasized how this condition should be evaluated and how the girl was managed. doi: 10.3329/taj.v21i2.3802 TAJ 2008; 21(2): 177-179